The last Khan of Khans - Marshall, Robert (Princeton : Films for the Humanities and Sciences [production company] ; Kuala Lumpur : Visual Resources [distributor], 1994)
This program traces the life of the fifth Great Khan, Kublai Khan, who preferred to make his home in China, where he ruled as the first emporer of the Yuan dynasty
Director for NHK, Ganji Eto, Tomohidae Terai ; executive producer for NHK, Takashi Inoue
Narrator : Sean Barrett
Keywords: Kublai Khan, -- 1216-1294; China -- History -- Yuan dynasty, 1260-1368